The Gene business who should control biotechnology? - Yoxen, Edward (Crucible : Science in Society, 1983)
Names corporations, scientists, and universities now manufacturing man-made organisms for medicine, agriculture and animal breeding, and chemistry, pointing out the potential for unconsidered & disastrous consequences beyond commercial success.